Cape Verde : 2002 Article IV Consultation, First Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria-Staff Report; Staff Statement; Public Information Notice and News Brief on the Executive Board Discussion; and Statement by the Executive Director for Cape Verde. (IMF Staff Country Reports; Country Report ;, 2003)
In recent years, the IMF has released a growing number of reports and other documents covering economic and financial developments and trends in member countries. Each report, prepared by a staff team after discussions with government officials, is published at the option of the member country.